Dynamics of inclined CNTRC sandwich beams under a moving mass with influence of CNT agglomeration - Tran, Thi Thom; Nguyen, Dinh Kien (Comptes Rendus. Mécanique)
Dynamics of inclined carbon nanotube (CNT) reinforced composite beams under a moving mass with influence of CNT agglomeration is studied. The beams compose of a homogeneous core and two composite face layers with effective properties being estimated by Eshelby–Mori–Tanaka approach. A novel finite element formulation is formulated and used to establish the equation of motion. Dynamic response is computed for a simply supported beam by Newmark method. The result reveals the important role of the CNT agglomeration on the dynamic response. The effects of the mass velocity, inclined angle and agglomeration parameters on the dynamic behavior are investigated in detail.